Analisis dan Peramalan Volume Produksi Semen Bulk Menggunakan Metode Time Series di PT. VT - Erlangga, Veto Andhika; Pulansari, Farida (Industrika : Jurnal Ilmiah Teknik Industri, 2025)
PT VT is a company engaged in the cement industry, particularly in the distribution of bulk cement through the Jetty Department. To enhance operational efficiency, PT. VT aims to forecast the volume of bulk cement for the upcoming period and determine the most effective forecasting method to utilize. This study will employ three forecasting methods: Moving Average (MA), Weighted Moving Average (WMA), and Single Exponential Smoothing (SES). Historical data on bulk cement volume over the past 11 months were analyzed, and the accuracy of the forecasts was evaluated using Mean Squared Error (MSE). The analysis results indicate that the Moving Average method produced an MSE of 678,038, the Weighted Moving Average yielded 587,301, and the Single Exponential Smoothing resulted in 493,586. Based on these findings, the Single Exponential Smoothing method is identified as the best forecasting method due to its lowest error rate compared to the other methods. By implementing this method, PT. VT can enhance forecasting accuracy, optimize distribution schedules, and minimize operational risks such as overstock or stock shortages. Consistent application of this method is expected to support supply chain sustainability and improve the company's overall operational efficiency. Keywords: Bulk Cement, Forecasting, Mean Squared Error, Operational Efficiency